Web based information system for fishery industry - Wong, Jie Jing (2022)

(untitled)
This project is a case-study based project, which is specific to the XIAN Fishery company. XIAN Fishery company is a traditional company which they are still using a traditional method to manage and operate their business, with handwriting for recording and calculate all the business operations data. The day-to-day business operation of the company is covered storekeeping, daily income records, payments and others. Due to problems like overstock or understock, data inaccurate, human mistakes in calculation and difficulty to summarize data, it causes a loss in money, integrity, and customer loyalty to the company. Therefore, this project is intended to develop an information system for the company in order to address issues their facing. The proposed system is a web-based system which allow user to access anytime, at least they have an Internet. The type of system development life cycle that used in this project is Rapid Application Development, this methodology enables the system to be developed in a systematic way. Besides, the expected benefits from this project are to allow company to manage the business information in a higher accuracy and efficiency way. The system will help the company to calculate and update the stock available amount on time. Thus, user can get the actual data. The company can manage customer or supplier information anytime whenever they needed, and all the order or purchase records can be linked to the specific supplier and customer. Furthermore, the system provides a reporting function in order to help the company to summarize the business information and generate different type of report based on their preference.